2021
DOI: 10.5198/jtlu.2021.1835
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with travel, ideal commuting, and accessibility to employment

Abstract: This paper explores relationships between commuting times, job accessibility, and commuting satisfaction based on a large-scale survey applied in the Greater London Area (GLA), the municipality of São Paulo (MSP) and the Dutch Randstad (NLR). Potential accessibility to jobs is estimated under 3 different scenarios: reported actual commuting times (ACT), ideal commuting times (ICT), and maximum willingness to commute (MCT). In addition, binary logistic regression models, estimated using generalized linear model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…Moreover, we found that the ACT positively correlates with both the ICT and MCT. These findings are consistent with Pritchard et al (2021).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Moreover, we found that the ACT positively correlates with both the ICT and MCT. These findings are consistent with Pritchard et al (2021).…”
Section: Discussionsupporting
confidence: 88%
“…Comparing to the findings of Redmond and Mokhtarian (2001) 1.2%, O'Fallon and Wallis (2012) 3%, Humagain and Singleton (2020) 8.4%, the percentage of people wanting an ICT of zero minutes in Jounieh is normal and lower than that in Portland, Oregon. Another study based on a survey applied in GLA, MSP, and NLR showed on average an ACT, ICT, and MCT of 29, 19, and 48 minutes, respectively (Pritchard et al, 2021). O'Fallon and Wallis (2012) also recorded a lower ACT (20 minutes) in Auckland and Wellington, as well as Humagain and Singleton (2020), ACT of 33.5 minutes in Portland, Oregon.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These three statistics are consistent with the data obtained by other researchers. Relevant studies have shown that the ICT is concentrated on 10 to 20 min ( 20 , 3335 ), while the acceptable or tolerable commute time is mainly distributed between 30 and 40 min ( 11 , 12 , 19 , 26 , 36 ). The average ICT, ACT, and TTCT in Kunming in 2014 were 18.6 min, 28.7 min, and 37.4 min, respectively ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…The theoretical basis for clustering the respondents using these three variables is that the ICT reflects commuters' preferences in terms of commuting times [50,53]. When the ACT is close to the ICT, the perceived satisfaction of commuters is better [41,43,78]. While the TTCT reflects commuters' tolerance of commuting times [57,58], When the ACT approaches or even exceeds the TTCT, the negative motions of commuters significantly increase [54], which leads to a sharp satisfaction decrease [40,42].…”
Section: Group Differences In the Nonlinear Relationships Between Com...mentioning
confidence: 99%